Analysis of the Role of Local Government in Empowering Rice Farmers (Case Study) - Kamarulah, Kamarulah; Djabar, Sadly Abdul; Suyuthi, Nurmadhani Fitri (Newinera Publisher, 2024)
This study aims to analyze the role of the local government in implementing the farmer empowerment program for rice farmers in Sumber Sari Village, Babulu District, Penajam Paser Utara Regency, and to assess the effectiveness of the program in improving farmers' productivity and welfare. Additionally, this study identifies and analyzes the challenges and obstacles faced by the local government in implementing farmer empowerment policies and seeks to understand how these factors influence the success of the program. This study employs a qualitative approach with a descriptive method. Data were collected through observation, in-depth interviews, and documentation, and then analyzed thematically. The findings indicate that the local government plays an active role in empowering farmers through the distribution of granular organic fertilizer funded by the DIPA APBD 1 of East Kalimantan Province. This program aims to enhance agricultural productivity by involving 28 farmer groups in Babulu District, including Sumber Sari Village. Although the program provides benefits to farmers, its effectiveness is still affected by limited access to water, a lack of technical extension services, and suboptimal agricultural infrastructure. The primary challenges in farmer empowerment include dependence on rainfall, land-use conversion, limited training opportunities, market price fluctuations, and the impacts of climate change. To improve the program’s success, this study recommends that the local government, particularly the Penajam Paser Utara Agricultural Office, expand farmers' access to subsidies and modern agricultural tools to enhance productivity. Additionally, future research could focus on the effectiveness of irrigation systems in strengthening food security.